2020
DOI: 10.1111/jonm.13113
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual climate in hospitals influences nurses’ professional quality of life

Abstract: Studies on workplace spirituality and health care workers' professional quality of life (ProQoL) have been expanding in recent years. Workplace spirituality within the health care system embodies one's efforts to pursue a meaningful and purposeful life; develop healthy relationships among colleagues, clients and families; and maintain coherent individual and organisational beliefs and values (Baldacchino, 2017). Spiritual climate (SC) is a common understanding among employees towards spirituality and the parta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 24 publications
4
27
1
5
Order By: Relevance
“…An article reporting the association between spiritual climate and ProQOL was previously published (Cruz et al, 2020). This article reports the findings of the analyses on the spiritual climate's impact on nurses' work engagement.…”
Section: Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…An article reporting the association between spiritual climate and ProQOL was previously published (Cruz et al, 2020). This article reports the findings of the analyses on the spiritual climate's impact on nurses' work engagement.…”
Section: Aimmentioning
confidence: 99%
“…We surveyed a convenience sample of 302 nurses employed in three Ministry of Health (MOH) hospitals in Riyadh region of Saudi Arabia. As reported by Cruz et al (2020), the nurses qualified for the study if they were registered nurses in the Saudi Commission for Health Specialties and were employed in one of the three hospitals for a minimum of 6 months regardless of nationality. The sample size was reported to have an adequate power with the post hoc power analysis revealing 99.4% power (effect size of 0.15 and margin of error of 0.05; Cruz et al, 2020).…”
Section: Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace spirituality as well as spiritual leadership is fundamental to quality of care, nurses' job satisfaction and motivation, so health care management needs to get a way to promote it. Cruz et al (2020) concluded that a positive spiritual climate of hospitals leads to improved 'compassion satisfaction' and low 'burnout' and 'secondary traumatic stress' among nurses, and therefore, policymakers, nursing leaders and nurses advocates are responsible for encouraging nurses spirituality, granting and respecting a place for different spiritual views aiming to improve the job satisfaction. Workplace spirituality is not yet totally implemented or neither a concern in most health care institutions.…”
Section: Workplace Spirituality In Health Care System-a Path To Satmentioning
confidence: 99%
“…Cruz et al. (2020) concluded that a positive spiritual climate of hospitals leads to improved ‘compassion satisfaction’ and low ‘burnout’ and ‘secondary traumatic stress’ among nurses, and therefore, policymakers, nursing leaders and nurses advocates are responsible for encouraging nurses spirituality, granting and respecting a place for different spiritual views aiming to improve the job satisfaction. Birnie (2019) calls for hospitals' responsibility in ensuring that libraries may facilitate literature on spirituality.…”
Section: Introductionmentioning
confidence: 99%